Membangun Hubungan Internal Yang Solid Untuk Menciptakan Iklim Komunikasi Positif Didalam Organisasi - Annisa Wahyuni Arsyad Wahyuni Arsyad (Prodi Ilmu Administrasi Negara, 2016)
Improving the way of organizational communication means improving organization itself comprehensively. Communications plays important role in creating an ideal organization, changing organization, and producing outcomes. Internal communication aims to integrate all the people within organization, and achieving a positive climate in organization itself. One of the core in theoritical study of Public Relations is how to build and maintain a good relationship with internal public, such as employee. Solid internal relationship is needed to achieve organization’s objectives, and furthur more it will influence toorganization’s image in external public point of view.